Novel triphosphorylation polyurethane nanoparticles for blood-contacting biomaterials' coating. Issue 6 (12th January 2016) - Zhang, Jun; Sun, Zhijun; Zhu, Haomiao; Guo, Qiaochu; He, Chengai; Xia, Ao; Mo, Hong; Huang, Xiaohua; Shen, Jian
Abstract : Novel polyurethane/sodium triphosphate nanoparticles were synthesized to enhance the blood compatibility of blood-contacting materials. Abstract : Improving hemocompatibility of biomaterials and devices contacting the human blood has been the subject of intensive research. In this study, we synthesized a novel excellent blood compatible polyurethane/sodium triphosphate nanoparticle (PU/STPP). Characterization of polyurethane/sodium triphosphate (PU/STPP) nanoparticles was carried out by transmission electron microscopy (TEM), scanning electron microscopy (SEM), dynamic light scattering (DLS), nuclear magnetic resonance (NMR), and energy dispersive spectroscopy (EDS). Blood compatibility assessment of PU/STPP nanoparticles was performed by in vitro coagulation time, plasma clotting time, hemolysis rate, and red blood cell morphology tests. Cell compatibility evaluations of PU/STPP nanoparticles were obtained by MTT cell viability tests. The PU/STPP nanoparticles also were used to modify vascular prostheses with cosedimentation. Platelet adhesion tests showed that blood compatibility of vascular prostheses coated with PU/STPP nanoparticles is better than that of pure vascular prostheses.